ANALISIS KELAYAKAN USAHA PETERNAKAN AYAM PETELUR PT NAGA PETERNAKAN DI DESA ULAPATO A KECAMATAN TELAGA BIRU KABUPATEN GORONTALO - Laha, Rahmad D; Halid, Amir; Bempah, Irwan (AGRINESIA : Jurnal Ilmiah Agribisnis, 2017)
This research aims to: 1) identify amount of production cost in laying hens business in Village of Ulapato A, Sub-district of Telaga Biru, District of Gorontalo, 2) analyze profit of laying hens business in Village of Ulapato A Subdistrict of Telaga Biru, District of Gorontalo, 3) analyze business suitability of laying hens in Village of Ulapato A Sub-district of Telaga Biru, District of Gorontalo. The research is conducted in company of PT Naga Peternakan in Village of Ulapato A, Sub-district of Telaga Biru, District of Gorontalo. The applied data analyses are financial suitability analysis, NPV, IRR and PBP. Research finding confirms that production cost in laying hens at PT Naga Peternakan comprises fixed price for IDR 133.268.299 and variable cost for IDR 2.143.548.714 and its total cost is IDR 2.276.817.013. Meanwhile, revenue of this business is IDR 3.553.420.000 with profit for IDR 1.276.602.987. Financially, livestock business of laying hens of PT Naga Peternakan is suitable to be developed and be run with value of NPV of 2,82 billion, IRR of 20,10 % and Pay Back Period of 3 years, 2 months and 24 days.